(untitled) (Global Journal of Human-Social Science, 2013)
The paper examines the issue of youth restiveness and insecurity in the Niger Delta as a whole and Delta State in particular. Youth restiveness and insecurity began with agitation and demands by the youths in the Niger Delta societies for their rights (economic, political and environmental rights), crystallizing into the inducement of the evolution and activities of youth restiveness and insecurity in the Niger Delta states in general and Delta State in particular. The data used for the study were obtained from the secondary sources and were analyzed using a quantitative method to ascertain the level of the existence and effects of youth restiveness and insecurity in Niger-Delta and particularly in Delta State. The paper reveals that youth restiveness and the high spate of insecurity in the Niger-Delta states and Delta State in particular has a very negative impact on the Niger Delta states, economy and the Nigerian society in general.